Matrix metalloproteinases 2 and 9 are elevated in human preterm laboring uterine myometrium and exacerbate uterine contractility†. Issue 6 (5th April 2019) - Ulrich, Craig C; Arinze, Veronica; Wandscheer, Carolina Bueno; Copley Salem, Christian; Nabati, Camellia; Etezadi-Amoli, Neda; Burkin, Heather R
Abstract: Matrix metalloproteinases 2 and 9 (MMP2/9) have previously been shown to be elevated in serum and amniotic fluid from women undergoing preterm birth. We performed experiments to determine the effects of MMP2/9 on uterine contraction and birth timing. Pregnant mice were injected daily with 50 mg/kg of SB-3CT or vehicle control beginning on gestational day 14–18 to determine if MMP2/9 inhibition would affect parturition timing. MMP2/9 expression in human myometrial tissue was determined by Simple Western (Wes) and semiquantitative western blot. Purified MMP2/9 and SB-3CT inhibitor were added to human myometrial strips to determine the effects of MMP2/9 on oxytocin-induced uterine contraction. Parturition was delayed in mice treated with MMP2/9 inhibitor SB-3CT. MMP2/9 protein levels were elevated in preterm laboring uterine myometrium. Gelatinase activity was confirmed in cell extracts and supernatants from immortalized and primary human uterine myometrial cells in culture. Addition of purified MMP2/9 increased the oxytocin-induced contractile response in myometrial tissue strips from pregnant women. In contrast, addition of the MMP2/9 inhibitor SB-3CT decreased the contractile response to oxytocin in a dose-dependent manner. These results suggest abnormal MMP2/9 expression affects the contractile state of the uterine myometrium to promote parturition and that MMP2/9 inhibition attenuates this effect. Abstract : Matrix metalloproteinases 2 and 9 are elevated in preterm laboring myometrium, promote myometrial contraction, and may contribute to parturition timing.